Implementasi Sistem Kehadiran Guru Berbasis Internet of Thing di SDIT Darul Hikmah - Amrullah, Ridhwan; Chusyairi, Ahmad (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
The teacher attendance system currently implemented at SDIT Darul Hikmah Jakarta still uses the manual method by filling in the arrival time and signing the attendance book available in the office. The system has several drawbacks such as manipulation of attendance, damaged or missing attendance books, and ineffective reporting because the general coordinator needs to copy back attendance data to be submitted to the principal and chairman of the foundation as material for evaluating teacher performance. Therefore, this study aims to create an Internet of Thing-based presence system using NodeMCU ESP 32 and a fingerprint sensor. This research process uses the Prototype method. This research produced a teacher attendance recorder that teachers can use as proof of attendance when they arrive at class. In addition, the website utilized to manage teacher attendance data to make reports and is used by teachers to fill out learning agendas that can provide feedback to student parents regarding student participation in learning through the Telegram application.